B1 corrected T1 mapping in the differentiation and prediction of breast cancer - Yijie Chen; Jichun Guo; Feifei Shan; Gehua Tong; Zhihua Meng; Zhensong Chen; Junqi Sun (Scientific Reports)
Abstract To explore the effect of B1-corrected T1 mapping on the differentiation of benign and malignant breast lesions and the prediction of biological characteristics in breast carcinoma. 364 patients with breast lesions were included. T1 maps were acquired with multi-flip angle imaging sequences before and after contrast enhancement. T1 values before (T1max, T1mean, T1min) and after enhancement (T1maxce, T1meance, T1mince) were measured. Difference in T1 (ΔT1), percentage reduction in T1(ΔT1%) and contrast-enhanced T1 ratio (T1mean/T1meance) were calculated. The differences in T1 values before and after enhancement between benign and malignant breast lesions were compared. Prediction models were constructed with clinical imaging data. The diagnostic efficiency of the prediction models was compared using ROC. DeLong test was used to compare the AUC of the models. Univariate analysis showed that T1mean, T1max, T1meance, T1mince, ΔT1, ΔT1%, T1mean/T1meance, maximum lesion diameter, age, and BI-RADS classification were statistical significance (p < 0.05) between benign and malignant lesions. Multivariate analysis showed that ΔT1%, age, and BI-RADS classification were independent risk factors. Model 1( ΔT1%, age, and BI-RADS classification) demonstrated superior diagnostic performance in differentiating benign from malignant breast lesions, with the AUC of 0.952 (95% CI: 0.926–0.977). B1-corrected T1 mapping has good clinical value for the differentiation of benign and malignant breast lesions.